2021
DOI: 10.1016/j.ijwd.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on dermatology practices: Results of a web-based, global survey

Abstract: Highlights This web-based, global survey of dermatologists showed a decrease in in-person consultations, hospital service, and procedures, a 3-fold increase in teledermatology use, and a shortage in PPE in the healthcare system. The number of COVID-19 cases in participant’s country was the most important prognostic factor of future teledermatology use. The pandemic had immediate impact on dermatology practice, and appears to have contributed to increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
0
34
0
3
Order By: Relevance
“…Across 12 dermatology clinics affiliated with Massachusetts General Hospital, most visits were scheduled live telephone calls where providers conversed with patients while viewing photographs uploaded in advance; asynchronous telemedicine visits comprised a minority (1 in 5) of all visits during April 2020. Potential advantages of asynchronous visits were the convenience of providers and patients operating on their own schedules ( 35 ). Similarly, the Department of Dermatology at Yale School of Medicine concluded that a hybrid between SAF and video proved most effective, using SAF prior to scheduled video calls to expedite visits ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Across 12 dermatology clinics affiliated with Massachusetts General Hospital, most visits were scheduled live telephone calls where providers conversed with patients while viewing photographs uploaded in advance; asynchronous telemedicine visits comprised a minority (1 in 5) of all visits during April 2020. Potential advantages of asynchronous visits were the convenience of providers and patients operating on their own schedules ( 35 ). Similarly, the Department of Dermatology at Yale School of Medicine concluded that a hybrid between SAF and video proved most effective, using SAF prior to scheduled video calls to expedite visits ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…With COVID-19, SAF proved especially helpful with patients with stable chronic diseases and/or longer-term medications (e.g. patients doing well and simply needing refills) ( 35 ). SAF was also useful in recognizing certain common diagnoses: acne, dermatitis, psoriasis, rashes, and rosacea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across 12 clinics affiliated with Massachusetts General Hospital, SAF asynchronous teledermatology accounted for 1 in 5 of all dermatology visits in April 2020 [48]. A web-based, global survey found that the use of teledermatology increased three-fold during the pandemic (26.1% vs. 75.2%), and that more than two thirds of respondents (68.6%) expect to continue teledermatology use in the future [49]. Unfortunately, many of the policy changes ensuring broad coverage for telehealth services covered under the pandemic are temporary, expanding only to the end of the public health emergency.…”
Section: Introductionmentioning
confidence: 99%